Influence of cerium (IV) ions on the mechanism of organosilane polymerization and on the improvement of its barrier properties - Suegama, P. H.; de Melo, H. G.; Benedetti, Assis Vicente [UNESP]; Aoki, I. V. (Pergamon-Elsevier B.V. Ltd, 2009)
In this work, the effect of cerium (IV) ammonium nitrate (CAN) addition on the polymerization of bis-[triethoxysilyl]ethane (BTSE) film applied on carbon steel was studied. The electrochemical characterization of the films was carried out in 0.1 mol L(-1) NaCl solution by open-circuit potential measurements, anodic and cathodic polarization curves and electrochemical impedance spectroscopy (EIS). Morphological and chemical characterization were performed by atomic force microscopy (AFM), contact angle measurements, infrared-spectroscopy, nuclear magnetic resonance and thermogravimetric analysis. The results have clearly shown the improvement on the protective properties of the Ce(4+) modified film as a consequence of the formation of a more uniform and densely reticulated silane film. A mechanism is proposed to explain the accelerating role of Ce(4+) ions on the cross-linking of the silane layer. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Silane; Cerium (IV) ammonium nitrate; Corrosion protection